Effect of Season on Diet Composition, Dry Matter Intake and Digestibility in Adult Sheep Grazed on Sub-Alpine Pastures of Kashmir Valley - Mir, Shahid H.; Haider, A.; Ahmed, A.; Ganai, A.M.; Afzal, Yasir (Indian Journal of Animal Nutrition, 2018)
The present study was designed to analyzes the seasonal variations in diet composition, nutrient intake and digestibility of sub-alpine pastures of Kashmir valley in mature sheep. The experiment was conducted in two seasons of summer (June) and autumn (October) at two locations (MRCSG, Shuhama, Location-I and SBF,Dachigam, Location-II) having different vegetative covers. The apparent digestibility of most of the nutrients was higher (P